Purification, Physicochemical Properties, and Antioxidant Activities of Two Low-Molecular-Weight Polysaccharides from Ganoderma leucocontextum Fruiting Bodies - Xiong Gao; Jiayi Qi; Chi-Tang Ho; Bin Li; Yizhen Xie; Shaodan Chen; Huiping Hu; Zhongzheng Chen; Qingping Wu (MDPI AG, 2021)
Two low-molecular-weight polysaccharides (GLP-1 and GLP-2) were purified from Ganoderma leucocontextum fruiting bodies, and their physicochemical properties and antioxidant activities were investigated and compared in this study. The results showed that GLP-1 and GLP-2 were mainly composed of mannose, glucose, galactose, xylose, and arabinose, with weight-average molecular weights of 6.31 and 14.07 kDa, respectively. Additionally, GLP-1 and GLP-2 had a similar chain conformation, crystal structure, and molecular surface morphology. Moreover, GLP-1 exhibited stronger antioxidant activities than GLP-2 in five different assays: 2,2'-azino-bis(3-ethylbenzthiazoline-6-sulfonic acid) (ABTS), hydroxyl radical, superoxide anion radical, ferric reducing antioxidant power (FRAP), and oxygen radical antioxidant capacity (ORAC). The main linkage types of GLP-1 were found to be →4)-α-D-Glcp-(1→, →4)-β-D-Glcp-(1→, →3)-β-D-Glcp-(1→, →6)-β-D-Galp-(1→, →6)-α-D-Glcp-(1→, →4,6)-α-D-Glcp-(1→, and Glcp-(1→ by methylation analysis and nuclear magnetic resonance (NMR) spectroscopy. In addition, GLP-1 could protect NIH3T3 cells against tert-butyl hydroperoxide (tBHP)-induced oxidative damage by increasing catalase (CAT) and glutathione peroxidase (GSH-Px) activities, elevating the glutathione/oxidized glutathione (GSH/GSSG) ratio, and decreasing the malondialdehyde (MDA) level. These findings indicated that GLP-1 could be explored as a potential antioxidant agent for application in functional foods.